A Review of the Antioxidant Activity of Celery (Apium graveolens L) - Kooti, Wesam (J Evid Based Complementary Altern Med, 2017)
Plants are an important source of natural active products that are different, based on mechanism and biological properties. Celery (Apium graveolens L) is a plant from the apiaceae family and phenolic and antioxidant compounds of this plant have been studied by several scientists. The aim of this study was to review systematically the antioxidant activity of celery. Required articles were searched from databases such as Science Direct, PubMed, Scopus, and Springer. Keywords used in this study were Apium graveolens L, celery, antioxidant, free radical, leaf, and seed. Out of 980 collected articles (published in the period 1997-2015), 9 studies finally met the inclusion criteria and were considered. Celery, because of compounds such as caffeic acid, p-coumaric acid, ferulic acid, apigenin, luteolin, tannin, saponin, and kaempferol, has powerful antioxidant characteristics, to remove free radicals. It is clear that celery, with different compounds and diverse concentration can have varied healing effects. It is suggested that the next studies concentrate on other therapeutic and industrial attributes of celery.